Successful management of catheter injury or refractory infection by partial replantation of peritoneal dialysis catheters: a retrospective observational study - Seyoung Ryou; Eun Jeong Ko; Hoon Suk Park; Byung Ha Chung; Cheol Whee Park; Chul Woo Yang; Yong-Soo Kim; Hyung Duk Kim; Yaeni Kim (BMC Nephrology)
Abstract Background The revised 2023 guidelines from the International Society for Peritoneal Dialysis (ISPD) emphasize salvage methods for treating refractory catheter-related infections, or mechanical catheter damage. This approach preserves the existing catheter by manipulating only the outer cuff above the peritoneum, avoiding hemodialysis transfer. We investigated the effectiveness of the partial replantation technique. Methods In this retrospective single-center study (January 2021 - December 2023), outcomes for nine patients undergoing salvage methods were compared with 58 patients receiving de novo catheter insertion. We assessed exit-site infection (ESI), tunnel infection (TI), peritonitis, and catheter dysfunction. The salvage method entailed distal cutting of the impaired catheter and attaching a new segment using a connector with a PD adaptor and transfer set. Results Nine patients (four males, mean age 56 years, average PD duration 66 months) employed the salvage method. Post-procedure, one patient (11.1%) reported ESI, one (11.1%) experienced TI, three (33.3%) developed peritonitis, and two (22.2%) required catheter removal. No procedural complications or catheter dysfunctions were observed. In the control group, ESI occurred in six patients (10.3%), TI in one (1.7%), peritonitis in 11 (19.0%), catheter removal in seven (12.1%), and catheter dysfunction in one (1.7%). Kaplan-Meier analysis showed no statistical difference between the groups: ESI (p = 0.306), TI (p = 0.094), peritonitis (p = 0.838), catheter dysfunction (p = 0.694), and catheter removal (p = 0.393). Conclusions This study supports the non-inferiority and effectiveness of the salvage method compared to de novo insertion in managing ESI or TI and mechanical catheter damage.